Biological Activities of Phytochemicals in Plants - Tuğba Demir; Özlem Akpınar (Turkish Journal of Agriculture: Food Science and Technology, 2020)
Bioactive compounds, called phytochemicals, are produced as secondary metabolites in plants that have beneficial effects on health when they are consumed as nutrients. Phytochemicals have an effective role in the formation of the color, smell and taste of the plants. As an alternative to the synthetic materials used in the treatment of many chronic diseases, the interest in the use of plants phytochemicals have been increased. This trend has led to the development of a new market. This review includes biological activities of plant phytochemicals including antioxidant, antimicrobial, antifungal, antidiabetic, antiinflammatory, anticancer and antihypertensive properties.